e)
[tex]1 \frac{2}{3} ab - 13a + 4.5ab - ab = ( \frac{5}{3} + \frac{9}{2} - 1)ab - 13a = ( \frac{10}{6} + \frac{27}{6} - \frac{6}{6})ab - 13a = \frac{31}{6}ab - 13a = 5 \frac{1}{6} ab - 13a [/tex]
f)
[tex]8.3ab - ab + 17ba + 8a - 11 = (8.3 - 1 + 17)ab + 8a - 11 = 24.3ab + 8a - 11[/tex]
g)
[tex]3 \frac{3}{5} az - 1 \frac{1}{5} z + 5za - za = (3 \frac{6}{10} + 5 - 1)az - 1 \frac{1}{5} z = (3.6 + 5 - 1)az - 1 \frac{1}{5}z = 7.6az - 1 \frac{1}{5} z[/tex]
h)
[tex]5.2xy - 3ab + 4ab - 5 \frac{1}{5} xy + 2 = (5.2 - 5 \frac{2}{10})xy + ab + 2 = (5.2 - 5.2)xy + ab + 2 = ab + 2 [/tex]